Learning Behavior Components as Predictors of Third-Grade Achievement in Banten - Reni Apriani; Abdul Qodir; Fuzi Arianto; Supaphorn Akkapin (Jurnal Pendidikan Progresif, 2026)
This study examines the partial and simultaneous effects of five learning behavior components: attitude, learning motivation, learning strategies, memory, and metacognition, on the academic achievement of third-grade students in Banten Province, Indonesia. A quantitative explanatory survey was conducted involving 94 third-grade students selected through intact-group cluster sampling from three public elementary schools in Serang, Cilegon, and Tangerang. Learning behavior was measured using Likert-scale questionnaires, and academic achievement was assessed using semester report card grades. Response quality was evaluated using the Rasch measurement model, and Ordinal Logistic Regression was employed for analysis. Results indicated that the overall model significantly predicted students' academic achievement (χ² = 12.414, p = 0.030; Nagelkerke pseudo-R² = 0.157). Among the five components, memory was the only statistically significant predictor (B = 0.215, OR = 1.24, p = 0.020), while attitude, learning motivation, learning strategies, and metacognition showed no significant unique effects. It is concluded that learning behavior is a multidimensional construct with unequal contributions from its components, and that memory emerged as the strongest independent predictor. These findings suggest that elementary teachers should prioritize instructional practices strengthening students' memory processes through retrieval practice and structured learning activities. Keywords: academic achievement, elementary school, learning behavior, memory, metacognition.